HUBUNGAN BEBAN KERJA PERAWAT DENGAN KELENGKAPAN PENGISIAN DOKUMENTASI ASUHAN KEPERAWATAN - etlida wati; Ulva Arini (Universitas Fort De Kock, 2020)
Documentation is an activity of recording, reporting or recording an event and activities carried out in the form of providing services that are considered important and valuable. One factor that can influence documentation is the nurse's workload. The purpose of this study is to identify the relationship between nurses' workload and the application of documentation in the Hj. Anna Lasmanah Banjarnegara. This research is quantitative with a cross sectional approach descriptive correlation design. Samples were taken with a total sampling of 65 nurses. Instruments to measure documentation using observation sheets. While the nurse workload instrument uses a questionnaire sheet. The analysis technique uses Spearman Rank correlation. Based on the research results of the workload of a nurse in the hospital room , most of them are in the weight category, as many as 46 respondents (70.8%). Application of nursing care documentation in the hospital room Hj. Anna Lasmanah Banjarnegara, most of them are respondents in the incomplete category as many as 63 respondents (96.9%). There is a significant relationship between nurse workload with the application of documentation, this is evidenced by the results of the Spearman Rank correlation bivariate analysis, which is r = 0.688 with p = 0.000 <0.05. It is hoped that management will motivate nurses to complete the documentation of nursing care